Geneva Health Forum 2020 Poster Book - Flahault, Antoine; Geissbuhler, Antoine; Rosset, Nicole (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
From 16 to 18 November 2020, the eighth edition of the Geneva Health Forum, which took place in the difficult context of the Covid 19 pandemic, hosted 165 posters. The present collection offers through 65 posters a wide range of topics discussed.